Wind‐Driven Strain Extends Seasonal Stratification. Issue 22 (27th November 2019) - Ruiz‐Castillo, Eugenio; Sharples, Jonathan; Hopkins, Jo
Abstract: The onset and breakdown of stratification are key physical drivers of phytoplankton growth in shelf seas and the open ocean. We show how in the Celtic Sea, where seasonality in stratification is generally viewed as controlled by heat input, a cross‐shelf salinity gradient horizontally strained by the wind prolonged the stratified period by 5–6 days in autumn prior to full winter mixing, while in spring caused seasonal stratification to begin 7 days early. Salinity straining has important implications for setting light conditions during the start of the spring bloom and for the timing of bottom‐water ventilation in winter. Analysis of winds around the time of likely onset of spring stratification between 1979 and 2016 showed that in 60% of the years' wind conditions were favorable for salinity straining. Accurate knowledge of the horizontal salinity field and wind stress are required to correctly determine the onset and breakdown of stratification. Key Points: A cross‐shelf salinity gradient combined with wind‐driven transport generates salinity strain that maintains/extends seasonal stratification Extending/maintaining the stratified period has implications for the timing of the phytoplankton bloom and bottom water ventilation Models do not reproduce the observed cross‐shelf salinity gradients and fail to simulate the timing and duration of phytoplankton blooms